Web-Based Design Of Admission Information System In Sma Negeri 1 Tulung Selapan - Muhammad hafis imthihan anjasman Imthihan; Karnadi (International Journal Cister, 2022)
SMK N 1 Tulung Selapan is one of the senior high schools in the Tulung Selapan area which is engaged in education. From year to year prospective new students always increase. For now, the selection process for new admissions is still using the manual system by registering directly to the school. In today's increasingly developing era, the registration process can actually be done without having to come directly to school, so that it can make it easier for parents or prospective students to register new students more quickly and effectively. Based on this, an online registration information system was designed for web-based new student admissions.